Roles of FACTS Devices in Modern Transmission: A Review of Challenges, Solutions, and Research Direction - Sabo Aliyu; Sadiq N. Buba (Universitas Negeri Surabaya or The State University of Surabaya, 2026)
Flexible AC Transmission Systems (FACTS) play a critical role in enhancing the stability, controllability, and efficiency of modernpower transmission networks. This review examines the main FACTS devices—SVC, STATCOM, TCSC, SSSC, and UPFC—coveringtheir classifications, working principles, integration methods, and comparative performance. Detailed schematics and tables are used to clarify their operation, highlight technical overlaps, and map device capabilities to specific system challenges. Key issues such as cost, control complexity, dynamic performance, and harmonic distortion are critically assessed, with proposed cross-device solutions and hybrid configurations presented to address these limitations. The review further emphasizes emerging trends, including AI-drivencontrol strategies, hybrid FACTS architectures, and applications in renewable-rich smart grids. By combining comparative insights witha forward-looking perspective, this paper provides guidance for engineers, researchers, and policymakers on deploying FACTS technologies to build more resilient, adaptive power systems.